Qualitative Assessment of Fire Safety of Commercial Buildings in Awka Anambra State, Nigeria - , Ndidi Blessing Iheama, Ani Ozioma Favour, Alintah -Abel Uchechi. V (Archives of Current Research International, 2025)
Background: This study investigates the challenges affecting the implementation of fire safety measures in commercial buildings in Awka, Anambra State, Nigeria. With rapid urbanization and commercial growth, Awka faces increased fire risks due to inadequate fire safety infrastructure, regulatory enforcement, and public awareness. Materials and Methods: Using a descriptive survey design, data were collected from 213 industry professionals, including architects, structural engineers, and builders, who directly influence fire safety practices. The primary data collection tool was a structured questionnaire analyzed through frequency analysis and the relative importance index (RII). Aim: The study seeks to assess challenges affecting the application of fire safety measures in commercial buildings in Awka, Anambra State, with a view to recommending more efficient fire management approaches. Results: The findings reveal several key barriers: inadequate regulatory enforcement, financial constraints, lack of technical expertise, and limited public engagement in fire safety practices. Additionally, insufficient fire safety training and lack of routine drills contribute to the low preparedness of building occupants during emergencies. Conclusion and Recommendation: The study underscores the need for stricter regulatory oversight, financial support for safety investments, enhanced technical training for local professionals, and mandatory safety drills for occupants. These strategies are essential to improve compliance with fire safety standards, mitigate fire risks, and safeguard lives and property in Awka’s commercial spaces. This research highlights significant areas for improvement, offering valuable insights for policymakers, industry professionals, and stakeholders in fire safety management. The research concludes that the Key challenges identified include financial constraints which were the primary obstacle, limited technical expertise, and inadequate enforcement of fire safety regulations. The study recommends enhanced Regulatory Enforcement and Oversight and Financial Assistance Programs for Fire Safety Improvements. It also recommends development of Technical Training and Certification Programs.